Social Work and Child Protection in Australia: Whose Job is it Anyway?. Issue 2 (14th March 2016) - Gillingham, Philip
Abstract : At the release of Professor Eileen Munro's final report of her review of child protection services in England and Wales, debate began in Australia about how her recommendations could be applied to reform and improve services in Australia. One particularly strong theme within the report is the need to strengthen professional social work as part of the reform of child protection services. However, as social work is not the key profession in child protection services in Australia, the direct applicability of Munro's recommendations is limited. The emphasis on the centrality of the social work profession to the provision and reform of child protection services is highly pertinent though as workforce development features strongly in Australian proposals for service reform. In this article, the reasons why 'child protection business' is not 'social work business' are explored historically and currently, with the aim of stimulating debate about who is employed in child protection services. Using Australian child protection services as a case study, the article also makes a contribution to debates about the international project of social work and the transferability of ideas for reform across international borders.